Hubungan Antara Status Sosial Ekonomi Orang Tua dan Efikasi Diri dengan Minat Menjadi Guru Mahasiswa Program Studi Pendidikan Teknik Elektro Universitas Negeri Jakarta - Parjiman; Nur Hidayanti; Suyitno M (Journal of Electrical Vocational Education and Technology, 2020)
Abstract The purpose of this study is to discover the level of strength: (1) relationship between parents’s sosio-economic status with interest to become a teacher (2) relationship between self-efficacy with interest to become a teacher (3) relationship between parents’s sosio-economic status with self-efficacy (4) relationship between parents’s sosio-economic status and self-efficacy with interest to become a teacher with a of population 90 people and using a sample of 72 people, namely students of educational elekctrical engineering study program in State University of Jakarta. This study uses a quantitative method with analysis prerequisite test using normality test and linearity test, then the data is analyse by hypothesis testing, t-test and F-test with the significance level of 5%. Based on the result hypothetical test calculation can be concluded: (1) There is a positive and significant relationship between parents’s sosio-economic status with interest to become a teacherseen from the value of rcount = 0,551> rtable = 0,232 and tcount = 5,528> ttable = 1,994. In line with several studies that have been explained in section 4.4 of the results and discussion, that these studies also illustrate the existence of a relationship between parents’s sosio-economic status with interest to become a teacher. (2) there is a positive and significant relationship relationship between self-efficacy with interest to become a teacher seen from the value of rcount = 0,682> rtable = 0,232 and tcount = 7,796 > ttable = 1,994. In line with several studies that have been explained in section 4.4 of the results and discussion, that these studies also illustrate the self-efficacy with interest to become a teacher. (3) There is a positive and significant relationship between parents’s sosio-economic with self-efficacy seen from the value of rcount = 0,528 > rtable = 0,232 and the value of tcount = 5,19512 > ttable = 1,994. (4) There is a positive and significant relationship between parents’s sosio-economic status and self-efficacy with interest to become a teacherseen from the value of rcount = 0,718> rtable = 0,232 and Fcount = 36,7364 > Ftable = 3,13. In line with several studies that have been explained in section 4.4 of the results and discussion, that these studies also illustrate the existence of a relationship between parents’s sosio-economic status and self-efficacy with interest to become a teacher. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui tingkat keeratan hubungan (1) hubungan antara status sosial ekonomi orang tua dengan minat menjadi guru, (2) hubungan antara efikasi diri dengan minat menjadi guru, (3) hubungan antara status sosial ekonomi orang tua dengan efikasi diri, (4) hubungan antara status sosial ekonomi orang tua dan efikasi diri dengan minat menjadi guru dengan populasi sebanyak 90 orang dan jumlah sampel 72 orang.Penelitian ini menggunakan metode kuantitatif dengan uji prasyarat analisis menggunakan uji normalitas dan uji linieritas kemudian data dianalisis menggunakan uji hipotesis, uji-t dan uji-F dengan taraf signifikansi 5%. Berdasarkan hasil perhitungan uji hipotesis dapat disimpulkan: (1) Terdapat hubungan yang positif dan signifikan antara status sosial ekonomi orang tua dengan minat menjadi guru dilihat dari nilai rhitung = 0,551 > rtabel = 0,232 dan nilai thitung = 5,528. > ttabel = 1,994. Sejalan dengan beberapa penelitian yang telah dijelaskan pada sub bab 4.4 tentang hasil dan pembahasan, bahwa penelitian-penelitian tersebut juga menggambarkan terdapatnya hubungan antara status sosial ekonomi orang tua dengan minat menjadi guru. (2) Terdapat hubungan yang positif dan signifikan antara efikasi diri dengan minat menjadi guru dilihat dari dari nilai rhitung = 0,682 > rtabel = 0,232dan nilai thitung = 7,796 > ttabel= 1,994. Sejalan dengan beberapa penelitian yang telah dijelaskan pada sub bab 4.4 tentang hasil dan pembahasan, bahwa penelitian-penelitian tersebut juga menggambarkan terdapatnya hubungan antara efikasi diri dengan minat menjadi guru. (3) Terdapat hubungan yang positif dan signifikan antara status sosial ekonomi orang tua dengan minat menjadi guru dilihat dari nilai rhitung = 0,534 > rtabel = 0,232 dan nilai Fhitung= 5,195 => Ftabel = 1,994. (4) Terdapat hubungan yang positif dan signifikan antara status sosial ekonomi orang tua dan efikasi diri dengan minat menjadi guru guru dilihat dari dari nilai rhitung = 0,718 > rtabel = 0,232 dan nilai Fhitung = 36,7364 >Ftabel = 3,13. Sejalan dengan beberapa penelitian yang telah dijelaskan pada sub bab 4.4 tentang hasil dan pembahasan, bahwa penelitian-penelitian tersebut juga menggambarkan terdapatnya hubungan antara efikasi diri dengan minat menjadi guru.